SPF Test from Baccaurea lanceolata Muell.Arg Fruit Isolates - Samsul Hadi; Subagus Wahyuono; Ag. Yuswanto; Endang Lukitaningsih (Indonesian Journal of Cancer Chemoprevention, 2017)
Not many researches on a fruit of limpasu (Baccaurea lanceolata Muell. Arg ) were found, while the use by tribal hamlets in Kalimantan already became a daily routine before they went into the field with the way made powder and smeared on the face. Therefore, the research on active substances needs to be done. For this study, we prepared two isolates which coded as K2 and CE, K2 from qualitative test negative isolates phenolic groups was identified by spray FeCl3, whereas qualitative test positive isolates were coded as CE and detected by a nitrogen-containing reagents dragendorf spray. The K2 isolate from SPF test resulted an SPF value of 3.2 at a concentration of 0.2 mg/ml, while CE isolate was given a value of SPF 5.0 at a concentration of 0.2 mg/ml. According to sensitivity skin test on rabbit skin, both K2 and CE isolated were given the value below 1, indicated the isolates were found to not irritate. This study proposes the potential from Baccaurea lanceolata Muell.Arg fruit isolates to be developed as a sunscreen for UV-protection.Keywords : Baccaurea lanceolata Muell.Arg, SPF test, sensitivity skin test